2022
DOI: 10.53730/ijhs.v6ns6.9700
|View full text |Cite
|
Sign up to set email alerts
|

Comparative study of percutaneous catheter drainage versus percutaneous needle aspiration for liver abscess

Abstract: This study aimed to assess the effectiveness and safety of percutaneous needle aspiration (PERCUTANEOUS NEEDLE ASPIRATION) and percutaneous catheter drainage (PER CUTANEOUS DRAINAGE  ) in the treatment of liver abscess. Methods: A prospective randomized study was conducted in patients presenting to Department of Surgery, GMERS Medical College, Vadodara between July 2019 and May 2022. 50 patients with liver abscess were randomized into two groups A and B. Complete history, presenting symptoms, medications were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“…We assessed the quality of the included studies according to the Cochrane risk of bias tool ( 34 ), as shown in Figure 2 . All of the included trials had a low risk of random sequence generation bias except Abusedera et al 2014 ( 18 ), Bansal et al 2015 ( 20 ), Gajera et al 2022 ( 22 ), Hanumathappa et al 2016 ( 24 ), Kulhari et al 2019 ( 25 ), and Rajak et al 1998 ( 26 ) with an unclear risk of selection bias. All the included studies had a low risk of allocation concealment bias except Abusedera et al 2014 ( 18 ), Ahmed et al 2021 ( 19 ), Batham et al 2016 ( 21 ), Bansal et al 2015 ( 20 ), Gajera et al 2022 ( 22 ), Hanumathappa et al 2016 ( 24 ), Kulhari et al 2019 ( 25 ), and Rajak et al 1998 ( 26 ) with an unclear risk.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…We assessed the quality of the included studies according to the Cochrane risk of bias tool ( 34 ), as shown in Figure 2 . All of the included trials had a low risk of random sequence generation bias except Abusedera et al 2014 ( 18 ), Bansal et al 2015 ( 20 ), Gajera et al 2022 ( 22 ), Hanumathappa et al 2016 ( 24 ), Kulhari et al 2019 ( 25 ), and Rajak et al 1998 ( 26 ) with an unclear risk of selection bias. All the included studies had a low risk of allocation concealment bias except Abusedera et al 2014 ( 18 ), Ahmed et al 2021 ( 19 ), Batham et al 2016 ( 21 ), Bansal et al 2015 ( 20 ), Gajera et al 2022 ( 22 ), Hanumathappa et al 2016 ( 24 ), Kulhari et al 2019 ( 25 ), and Rajak et al 1998 ( 26 ) with an unclear risk.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, all included trials had an unclear risk of reporting bias except Singh et al 2009 ( 27 ), Singh et al 2013 ( 29 ), and Singh et al 2019 ( 28 ), which had low risk. Finally, all of the included trials had a low risk of other bias except Ahmed et al 2021 ( 19 ), Bansal et al 2015 ( 20 ), Batham et al 2016 ( 21 ), Gajera et al 2022 ( 22 ), Hanumathappa et al 2016 ( 24 ), and Singh et al 2013 ( 29 ). Author judgments are furtherly clarified in Table S2 .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations